In Vitro Evaluation of Focused Ultrasound-Enhanced TNK-Tissue Plasminogen Activator-Mediated Thrombolysis - Papadopoulos, Nikolaos; Damianou, Christakis A. (My University, 2016)
The low and incomplete recanalization performance of thrombolytic therapy in patients with acute ischemic stroke has created the need to use focused ultrasound (FUS) energy as a way to enhance thrombolysis efficiency (sonothrombolysis). Using an in vitro flow model, the role of various parameters involved in FUS-enhanced tenecteplase (TNK-tPA [tissue plasminogen activator])-mediated thrombolysis was evaluated. Materials and methods Fully retracted porcine blood clots were used for the proposed parametric studies. A spherically FUS transducer (4 cm diameter), focusing at 10 cm and operating at 1 MHz, was used. Pulsed ultrasound protocols were applied that maintained temperature elevation at the focus that never exceeded 1°C. Thrombolysis efficiency was measured as the relative reduction in the mass of the clot. Results The role of various properties on thrombolysis efficacy was examined. These various properties are the acoustic power, the TNK-tPA concentration, the flow rate, the exposure time, the pulse length, the pulse repetition frequency, the duty factor, the formation of standing waves, the acoustic medium, and the administration of microbubbles. Study results have demonstrated that the parameters examined influenced thrombolysis efficacy and the degree of thrombolysis achieved by each parameter was measured. Conclusions Study findings helped us to optimize the treatment protocol for 1 MHz pulsed FUS that maximizes the thrombolytic efficacy of TNK-tPA, which potentially could be applied for therapeutic purposes. The outcome of the study showed poor thrombolysis efficacy, as with 30 minutes of FUS treatment only 370 mg of clot was removed.
Keywords: Ultrasound; Agar; Brain; Stroke